Pengaruh Tingkat Suku Bunga Terhadap Pertumbuhan Laba Pada PT. Bank Rakyat Indonesia Tbk, Cabang Salubarani Kabupaten Tanah Toraja Tahun 2020 – 2022 - Risda Risda; Syahrum Syahrum; Kamaruddin Kamaruddin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the effect of interest rates on profit growth of PT Bank Rakyat Indonesia Tbk Salubarani Branch Tana Toraja Regency. The data used in this study are secondary data and use data collection procedures, especially the documentation method. The data used in this study are financial statement data of PT Bank Rakyat Indonesia Tbk Salubarani Branch, Tana Toraja Regency. The results showed that the effect of interest rates on profit growth was very influential. The higher the interest given, the higher the profit growth.